Analisis Pengaruh Kinerja Keuangan Daerah terhadap Pertumbuhan Ekonomi di Provinsi Sulawesi Selatan - Rezkia Rezkia; Zikra Supri; Riyanti Riyanti (Al-Buhuts, 2023)
The purpose of this study was to determine the regional financial performance and economic growth of South Sulawesi Province from 2012 to 2021 because the success of a local government in regulating and funding its area can be seen from its financial performance and economic growth described in Law of the Republic of Indonesia Number 9 of 2015. The method used in this study is a quantitative method using secondary data. In producing the information in this study, ratio measurements were used. There are 3 ratios used, namely the independence ratio, the fiscal decentralization ratio, and the last is the PAD Effectiveness ratio. The results of this study are known that the ratio of independence has no effect and is significant on economic growth, on the ratio of fiscal decentralization with the same result that the ratio of independence has no effect and is significant on economic growth, while the ratio of effectiveness of PAD produces different results, namely the ratio of effectiveness of PAD has an effect and significant to economic growth.